2019
DOI: 10.1016/j.jseaes.2019.103878
|View full text |Cite
|
Sign up to set email alerts
|

Paleozoic to Cenozoic sedimentary bedrock geology and lithostratigraphy of Singapore

Abstract: A new lithostratigraphical framework for Singapore is proposed, based on the analysis of c. 20,000 m of core recovered from 121 c. 205 m deep boreholes and augmented with 218 field localities from across Singapore. The new framework describes a succession dating from the Carboniferous to the Quaternary. New U-Pb detrital zircon dates and fossil analysis were used to constrain the ages of key sedimentary units. The oldest known sedimentary rocks in Singapore are found to be the deformed Carboniferous (Mississip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Therefore it follows that the Bukit Timah fault is an approximately vertically dipping fault running throughout the crust. The presence of a significant fault also agrees with geological information showing that the ages of the two units are very similar (Dodd et al, 2019;Oliver & Manka, 2014). This suggests that significant tectonic movement must have occurred in order for sedimentary rocks to be adjacent to a granite pluton that formed at the same time.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore it follows that the Bukit Timah fault is an approximately vertically dipping fault running throughout the crust. The presence of a significant fault also agrees with geological information showing that the ages of the two units are very similar (Dodd et al, 2019;Oliver & Manka, 2014). This suggests that significant tectonic movement must have occurred in order for sedimentary rocks to be adjacent to a granite pluton that formed at the same time.…”
Section: Resultssupporting
confidence: 82%
“…However the geological structure beyond several hundreds of meters is almost entirely unknown. The near surface is composed of three principle geological units -Bukit Timah granite, Jurong Group metasediment and quaternary sediments (Dodd et al, 2019) (Figure 1a). The Bukit Timah granite underlies central Singapore and is the most extensive geological unit.…”
Section: Introductionmentioning
confidence: 99%
“…The Cretaceous zircons in the Temburong Formation sandstones were most likely ultimately derived from the Schwaner Mountains of South‐West Borneo where numerous Cretaceous plutonic, volcanic and metamorphic rocks are exposed (Breitfeld et al, 2020b; Davies et al, 2014; Hennig et al, 2017; Williams et al, 1988). Permian‐Triassic zircons are reported from the Malay‐Thai Tin belt (Dodd et al, 2019; Gillespie et al, 2019; Oliver et al, 2014; Searle et al, 2012; Sevastjanova et al, 2011) and Triassic zircons from the West Borneo province (Breitfeld et al, 2017; Hennig et al, 2017; Setiawan et al, 2013). Recently, Burton‐Johnson et al (2020) reported Triassic zircons from Triassic granitoids in eastern Sabah, which could also have provided a minor contribution.…”
Section: Discussionmentioning
confidence: 99%
“…However the geological structure below several hundred meters depth remains almost entirely unknown. The near surface is composed of three principle geological units-variegated arc-derived plutonic rocks and dykes of the Bukit Timah Center granite (Gillespie et al, 2019), very low metamorphic grade sediments of the Jurong Group, and Quaternary shallow marine and terrestrial sediments (Dodd et al, 2019; Figure 1a). The Bukit Timah Center granite underlies central Singapore and is the most extensive geological unit, representing repeated igneous intrusions into existing Carboniferous metamorphic basement between ∼285 and 230 Ma (Oliver et al, 2014).…”
Section: Geology Of Singaporementioning
confidence: 99%
“…The nature of the original relationship between the Jurong Group and the Bukit Timah Centre granite is not clear, as the contact does not crop out. While age constraints suggest the Jurong Group could have originally (Dodd et al, 2019). Outer coastline marks the current coastline of Singapore which is built on reclaimed land.…”
Section: Geology Of Singaporementioning
confidence: 99%